A national needs assessment study to determine procedures for simulation-based training in cardiology in Denmark. (2nd January 2019) - Gustavsen, Pia Helene; Nielsen, Dorte Guldbrand; Paltved, Charlotte; Konge, Lars; Nayahangan, Leizl Joy
Abstract: Objectives. New training methods such as simulation have been introduced in cardiology as in other specialties; however, the development of effective simulation-based training programs is challenging. They are often unstructured and based on convenience or coincidence. The objective of this study was to perform a nationwide general needs assessment to identify and prioritize technical procedures that should be included in a simulation-based curriculum for cardiology residency in Denmark. Design. We completed a needs assessment using the Delphi method among key opinion leaders in cardiology. Brainstorming in round 1 identified technical procedures that future cardiologists should learn. Round 2 was a survey to examine frequency of procedure, number of cardiologists performing the procedure, operator-related risk and/or discomfort for patients and feasibility for simulation. Round 3 was final elimination and prioritization of procedures. Results. Ninety-four key opinion leaders were included, and the response rates were 77% (round 1), 62% (Round 2), and 68% (Round 3). Twenty-four technical procedures were identified in Round 1 and pre-prioritized in Round 2. In round 3, 13 procedures were included in the final prioritized list. The five highly prioritized procedures eligible for simulation-based training were advanced life support, pleurocentesis, transesophageal echocardiography, coronary angiography, and pericardiocentesis. Conclusion. The general needs assessment following the Delphi process identified and prioritized 13 technical procedures in cardiology that should be integrated in a simulation-based curriculum. The final list provides educators a guide when developing simulation-based training programmes for cardiology residents.